A Study on Neck Injuries in Deaths Due to Hanging on Basis of Epidemiological Factors - Ashok Singh Dangus; Santosh Kumar Soni; Ranjan Mathur; Jitendra Acharya (Asian Journal of Medical Research, 2019)
Background: Most of the hanging cases are consider as suicidal until the homicidal and accidental are prove, because both homicidal and accidental hanging are rare. In these cases a watchful forensic examination plays an important role to determine the ante mortem character of the lesion and to exclude causes of hanging other than suicidal hanging. Aim: This study done to know the internal and external assessment findings among hanging cases. Subjects and Methods:Hanging deaths with external neck injuries along with ligature mark were included in this study. In this study a total of 60 cases of deaths due to hanging, was subjected to medico legal autopsy. Results:Most of the cases were observed in the age group of 21-40 years i.e., 41 (69.4%) out of 59 hanging deaths. Out of 59 deaths, 32 (54.2%) were females and 27 (45.7%) were males. Among neck structure injuries, majority of hanging cases had rupture / contusion of sternocleidomastoid and other strap muscles of neck, it was 57.6%. 33.8% cases had carotid intimal tear, 5% cases showed hyoid bone fracture and 3.3% thyroid cartilage. No fractures noted in Cricoid cartilage and cervical vertebra. Conclusion: Social awareness, problem solving and family support of most common age group is extremely necessary.